If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -10 = 30 Reorder the terms: -10 + y = 30 Solving -10 + y = 30 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + y = 30 + 10 Combine like terms: -10 + 10 = 0 0 + y = 30 + 10 y = 30 + 10 Combine like terms: 30 + 10 = 40 y = 40 Simplifying y = 40
| 4e-3(2e-2)=3(e+8) | | 3(4d-2)=3(d-2) | | 5(c-2)=3(c+6) | | 15x-4+4x+5+65= | | 7(b-4)=5(b-2) | | 2(3b-4)=5(b-1) | | 3(3a+1)=30 | | 4(1/3x-1/4)+4/3x/3+1=6 | | 8-4=6z-8z | | k^3+2k^2-10k-20=0 | | 7(x+2)=7x+10 | | z^4-26z^2+25=0 | | 5x-10-2=13 | | 1/2x16=0 | | p^(2/3)+p^(1/2) | | 3x-7+5=16 | | (x^2-81)/(x^2-6x-27)*(x+3)/x | | 98x+456= | | x^3-4x=85008 | | 250=(50-3)+x | | s=2x+t/r | | x/5-x=1/5 | | 0.5y=30 | | -6(x-2)+4(8x-12)=68 | | 6ln(3x)=12 | | -6(x-2)-4(8x-12)=68 | | 3x-2=7x+8 | | 4(-6+x)=5x+1/4 | | h=4a-3 | | 1/6-18/12 | | 7-3(5t-7)=67 | | 5x^2y^4-80x^4y^2=0 |